GRAMMATICAL OMISSION IN ENGLISH DESCRIPTIVE TEXTS: INSIGHTS FROM SECOND SEMESTER EFL LEARNERS - Dewi, Ekka Zahra Puspita; Ngaisah, Siti; Muliawan, Anugrah Adi; Hira, Salma; Darmanto, Darmanto (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study investigates grammatical omission errors in descriptive writing by second-semester EFL students at Madani Indonesia University. Using a descriptive qualitative approach, the research analyzed 45 student-written essays from a mid-term exam. Data were examined using Surface Strategy Taxonomy, focusing specifically on omission errors. The results revealed 239 total omission errors categorized into five types: articles (33.05%), pluralization (21.75%), punctuation (21.33%), verb phrases (12.97%), and conjunctions (10.87%). Article omission emerged as the most frequent. These errors often disrupted clarity, coherence, and grammatical accuracy. Findings highlight the influence of L1 interference and a limited grasp of basic grammar rules. The study underscores the need for focused instruction on articles, plurality, and structure to enhance students’ English writing accuracy and fluency.